2021
DOI: 10.1007/s00408-021-00477-z
|View full text |Cite
|
Sign up to set email alerts
|

4D Electromagnetic Navigation Bronchoscopy for the Sampling of Pulmonary Lesions: First European Real-Life Experience

Abstract: Purpose The use of Electromagnetic navigation bronchoscopy (ENB) for the diagnosis of pulmonary peripheral lesions is still debated due to its variable diagnostic yield; a new 4D ENB system, acquiring inspiratory and expiratory computed tomography (CT) scans, overcomes respiratory motion and uses tracked sampling instruments, reaching higher diagnostic yields. We aimed at evaluating diagnostic yield and accuracy of a 4D ENB system in sampling pulmonary lesions and at describing their influencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
(48 reference statements)
0
3
0
1
Order By: Relevance
“…During upper tract endourology, complications such as pyelorenal backflow, sepsis, and renal damage are directly related to increased intra-renal pressure. Duration of increased intra-renal pressure and concomitant obstruction are independent predictors of complication development [38] . Therefore, it might be reasonable to include an intra-renal pressure measurement, although the thin wire as used by the Chinese group seems to be complicated to place in the renal caliceal system.…”
Section: Discussionmentioning
confidence: 99%
“…During upper tract endourology, complications such as pyelorenal backflow, sepsis, and renal damage are directly related to increased intra-renal pressure. Duration of increased intra-renal pressure and concomitant obstruction are independent predictors of complication development [38] . Therefore, it might be reasonable to include an intra-renal pressure measurement, although the thin wire as used by the Chinese group seems to be complicated to place in the renal caliceal system.…”
Section: Discussionmentioning
confidence: 99%
“…The study confirmed that the diagnostic yield was 68.3%, which was still lower than that of other bronchoscopy technologies in previous studies. 115…”
Section: Virtual Bronchoscopy Navigationmentioning
confidence: 99%
“…Korrespondierend zu unseren Daten illustrierten Ishiwata und Kollegen eine Sensitivität von 67 % bei 9 untersuchten Patienten, welche jedoch nicht signifikant höher war als bei konventioneller Bronchoskopie (5/9, 56 %). Auch eine größere retrospektive italienische Analyse an 103 Patienten ergab eine diagnostische Ausbeute von 68,3 % bei einer erfolgreichen Navigationsrate von 80,6 % [17]. In unserem kleinen Kollektiv fand sich eine ähnliche Erreichbarkeit des PPNs.…”
Section: Diskussionunclassified